Semantics of Cardinal Directions in Benguet Cultural Practices - Pelila, John Rey; Escobar, Von Ameri; Pilorin, Jessa Mariel; Wakat, Geraldine (Scholar: Human Sciences, 2025)
Purpose: Benguet is a province rich in cultural heritage; moreover, the significance of cardinal directions in their cultural practices should be given more attention. This study aimed to identify the cultural practices of Indigenous Peoples in Benguet that incorporated cardinal directions and revealed the meanings of the cardinal directions in these cultural practices. Research design, data, and methodology: A document review was used, and among the 38 documents reviewed, 20 unveiled Benguet cultural practices integrating cardinal directions. These were treated using profiling through descriptive statistics and thematic analysis. Findings: It was revealed that cardinal directions are mainly seen in burial practices, but other practices also used these directions in pig slaughtering, customary law, trading, weaving, and weather forecasting. Constant practice was common in the four cardinal directions; however, each also has its distinct meanings: East is associated with supernatural intervention, eternity, passage to the afterlife, and women’s earthly responsibilities and afterlife authority; North signifies environmental wealth and receptivity; West is linked to discoveries and opportunities, and men’s earthly responsibilities and afterlife disposition; and South means unfavorable meteorological conditions. Conclusions: Therefore, it is concluded that cardinal directions play a significant role in cultural practices in Benguet as they highlight a deep connection between the people’s beliefs and these directional aspects of their environment, which are still applied due to their lasting cultural significance.